2021
DOI: 10.1177/13591053211059388
|View full text |Cite
|
Sign up to set email alerts
|

Relative deprivation and social anxiety among Chinese migrant children: Testing a moderated mediation model of perceived control and belief in a just world

Abstract: To examine the relationship between relative deprivation and social anxiety, which affects mental health, and investigate the mediating role of perceived control and the moderating role of belief in a just world (BJW) in an understudied population in Asia, we surveyed 1573 rural-to-urban migrant children (48% female; Mage = 12.3, SD = 1.7) in southeast China. Relative deprivation was positively correlated with social anxiety; perceived control partially mediated this connection. Moreover, BJW moderated the ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 130 publications
1
10
0
Order By: Relevance
“…Higher scores indicated higher self-esteem. This scale has been used with good reliability and validity in a sample of Chinese migrant children ( Xiong and Liu, 2020 ). In the current study, the items demonstrated good internal consistency and construct validity (Cronbach’s α = 0.80, χ 2 / df = 4.42, CFI = 0.97, TLI = 0.95, RMSEA = 0.05; CR = 0.77).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Higher scores indicated higher self-esteem. This scale has been used with good reliability and validity in a sample of Chinese migrant children ( Xiong and Liu, 2020 ). In the current study, the items demonstrated good internal consistency and construct validity (Cronbach’s α = 0.80, χ 2 / df = 4.42, CFI = 0.97, TLI = 0.95, RMSEA = 0.05; CR = 0.77).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, numerous studies indicate that BJW is an effective moderator ( Osborne and Sibley, 2013 ; Xiong and Liu, 2020 ). For example, research has shown that BJW moderates the relationship between relative deprivation and depression in left-behind children ( Xiong and Liu, 2020 ). Taken together, BJW may serve as a buffer in the relationship between relative deprivation and self-esteem.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…This was measured using the Relative Deprivation Scale for Migrant Children ( 62 ), which had good reliability and validity for Chinese migrant children ( 63 ). The scale included 20 items categorized into four dimensions: cognition of individual relative deprivation, the emotion of individual relative deprivation, cognition of group relative deprivation, and the emotion of group relative deprivation.…”
Section: Methodsmentioning
confidence: 99%
“…The structure of the family functions most effectively when family members maintain healthy relationships, interact together to solve problems, communicate effectively with other family numbers, and care for each other (Epstein et al, 1985). During migration, family function is likely to be impaired by the changing family structure and the acculturation stress of migration (Xiong et al, 2021; Yuan et al, 2019). As such, growing up in a dysfunctional family (e.g., ineffective communication within family numbers, poor family relationships, and maladaptive problem‐solving strategies; Mousavi, 2004) may leave migrant children emotionally scarred and affect their emotional adjustment (Wang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%